2017
DOI: 10.1080/03009742.2017.1334814
|View full text |Cite
|
Sign up to set email alerts
|

Describing and expanding the clinical phenotype of anti-MDA5-associated rapidly progressive interstitial lung disease: case series of nine Canadian patients and literature review

Abstract: In an inpatient setting, RPILD associated with characteristic skin rashes, profound weight loss, articular symptoms, normal or low CK with elevated ferritin, and absent fluorescence on ANA testing should alert the clinician to the possibility of MDA5-RPILD. T-cell-mediated therapies may play a role in this highly lethal condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 76 publications
2
20
1
Order By: Relevance
“…ILD is frequently rapidly progressive [46] explaining the poor survival rate of the disease (59-75%) [40 , 41] . Moreover, up to two thirds of the patients have polyarthritis [47] . Of note, even though anti-MDA5-positive DM is not associated with an increased risk of malignancy, the disease remains the most severe, in term of mortality, compared to all other forms of myositis.…”
Section: Dm Subtypesmentioning
confidence: 99%
“…ILD is frequently rapidly progressive [46] explaining the poor survival rate of the disease (59-75%) [40 , 41] . Moreover, up to two thirds of the patients have polyarthritis [47] . Of note, even though anti-MDA5-positive DM is not associated with an increased risk of malignancy, the disease remains the most severe, in term of mortality, compared to all other forms of myositis.…”
Section: Dm Subtypesmentioning
confidence: 99%
“…Although our research showed that relatively lower WBC counts and CRP levels are risk factors, the magnitude of its impact on prognosis is relatively limited. Numerous studies have con rmed that elevated serum ferritin is an independent risk factor for RP-ILD and poor prognosis in IIM patients [16,17,26,[29][30][31][32]. Our results showed that the elevation of serum ferritin still brings a trend of poor prognosis in IIM patients admitted to the ICU because of acute respiratory failure, although the statistical difference is not signi cant enough.…”
Section: Discussionmentioning
confidence: 45%
“…On the other hand, plasma exchanges represent a reasonable alternative for refractory cases, though adverse events such as allergy cannot be predicted (25). Altogether, combined immunosuppressive therapies, possibly by adjunction of mycophenolate and/or tacrolimus, give promising results (26). Large prospective studies are still lacking to identify the optimal treatment in anti-MDA5 positive patients with RP-ILD, but the scarcity of such patients will most likely require the set-up of multicenter clinical trials.…”
Section: Discussionmentioning
confidence: 99%